A condição internacional de Taiwan e a abertura de canais diplomáticos submersos como janela de oportunidade: o caso do CSCAP - 10.5102/uri.v8i2.1315 - da Silva, Jorge Tavares (2010)
The present essay focuses on the unique case of the island of Taiwan, a de facto, but not de jure state in the Asian context, lacking recognition from the international community, which leaves the territory in an exceptional state of isolation in the global institutional architecture. Unable to participate in many regional organisms, especially those that focus on security issues, Taiwan cannot present to multilateral fora the conflict with the People's Republic of China (PRC). The islanders have benefitted from a set of processes and networks of submerged nature, led by non-official actors, of which The Council for Security Cooperation in the Asia Pacific (CSCAP) has been a good example, and is here analysed.